Intestinal Microbiome-Metabolome Responses to Essential Oils in Piglets - Li, Yuan; Fu, Xiongfeng; Ma, Xin; Geng, Shijie; Jiang, Xuemei; Huang, Qichun; Hu, Caihong; Han, Xinyan (Frontiers in Microbiology, 2018)
This study investigated the effects of dietary essential oils (EOs) on intestinal microbial composition and metabolic profiles in weaned piglets. The piglets were fed the same basal diet supplemented with EOs (EO) or without EOs (Con) in the current study. The results showed that the body weight gain was significantly increased, while the diarrhea incidence was significantly reduced in the EO group. In addition, EOs could modify the intestinal microbial composition of weaned piglets. The relative abundances of some beneficial bacterial species such as Bacilli, Lactobacillales, Streptococcaceae and Veillonellaceae were significantly increased in the EO group. Metabolomics analysis indicated that protein biosynthesis, amino acid metabolism and lipid metabolism were enriched in the EO group. And correlation analysis demonstrated that some gut bacterial genera were highly correlated with altered gut microbiota–related metabolites. Taken together, this study indicated that dietary EOs not only altered microbial composition and function but modulated the microbial metabolic profiles in the colon, which might help us understand EOs’ beneficial effects on intestinal health of weaned piglets.